INFLUENCE OF BUSINESS DIGITALIZATION ON THE OIL RECOVERY FACTOR AND IMPROVING THE EFFICIENCY OF THE OIL AND GAS COMPANIES ACTIVITY - A. D. Balashova; O. I. Bolshakova (Вестник университета)
Against the background of the decline structure of hydrocarbon reserves in Russia, the maintenance of a stable level of production and enhanced oil recovery at mature fields is associated with the introduction of technologies of the fourth industrial revolution (Industry 4.0). The real and possible impact of digitalization on the oil recovery factor and impact of the technological solutions on the development hard-to-recover reserves have been сonsidered in the article. Special attention has been paid to the transition to intellectual methods of management, within the framework of digitalization, which ensure the effective management for all company’s processes, provide objective and transparent information for making accurate and operational management decisions. To ensure a significant effect from the digital transformation of the industry, it is necessary to create favorable investment conditions, including government regulation and stimulation.